1979
DOI: 10.1128/jcm.10.6.903-909.1979
|View full text |Cite
|
Sign up to set email alerts
|

Immune response and prevalence of antibody to Norwalk enteritis virus as determined by radioimmunoassay

Abstract: A solid-phase microtiter radioimmunoassay was established for the detection of Norwalk virus and its antibody, with clinical materials from human volunteers previously studied in Massachusetts as reagents. A study of 308 Massachusetts residents showed that serum antibody to Norwalk agent was rarely present during childhood but was detectable in approximately 50% of adults. All volunteers inoculated with Norwalk virus who developed illness seroconverted (10/10), whereas only one-third (5/15) of nonill volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(43 citation statements)
references
References 24 publications
4
39
0
Order By: Relevance
“…An unusual pattern of immunity is seen in norovirus infections. Pre-existing serum antibody to norovirus is not associated with protective immunity, and persons with higher levels of pre-existing antibody are in fact more likely to experience symptomatic disease in most (Blacklow et al 1979;Johnson et al 1990) but not all studies (Madore et al 1990). Graham et al (1994) challenged 50 adult volunteers with the 8FIIa inoculum and reported 82% of them became infected and 68% had symptoms of illness.…”
Section: Norovirusmentioning
confidence: 99%
See 1 more Smart Citation
“…An unusual pattern of immunity is seen in norovirus infections. Pre-existing serum antibody to norovirus is not associated with protective immunity, and persons with higher levels of pre-existing antibody are in fact more likely to experience symptomatic disease in most (Blacklow et al 1979;Johnson et al 1990) but not all studies (Madore et al 1990). Graham et al (1994) challenged 50 adult volunteers with the 8FIIa inoculum and reported 82% of them became infected and 68% had symptoms of illness.…”
Section: Norovirusmentioning
confidence: 99%
“…Norovirus challenge studies found that not all individuals are susceptible to norovirus infection and disease symptoms (Blacklow et al 1979;Graham et al 1994;Parrino et al 1977). These observations led to the hypothesis that there was a genetic resistance or susceptibility factor missing or present in some people.…”
Section: Norovirusmentioning
confidence: 99%
“…However, this pattern was not found in volunteer studies among adults. Blacklow et al [48] reported that ill volunteers challenged with Norwalk virus were more likely to have high than low serum antibody titers, and Parrino et al [49] showed that serum antibody titers to Norwalk virus were not protective against illness. They found that 6/12 individuals challenged with Norwalk virus developed clinical symptoms, whereas the other 6 persons remained asymptomatic.…”
Section: Is a Host Genetic Factor Associated With Resistance To Norovmentioning
confidence: 99%
“…RIA antigen and antibody detection assays were used to further characterize infection and illness in experimentally induced human infection (23,48,231), to perform seroprevalence studies in different populations (47), and to investigate outbreaks of gastroenteritis (14, 15, 46, 76, 92, 95, 98, 99, 141-144, 151, 169, 235, 253). The application of these assays helped identify NV and related viruses as a common cause of nonbacterial gastroenteritis outbreaks.…”
Section: Radioimmunoassaymentioning
confidence: 99%